Pig feed as a source of bacterial DNA and its potential impact on porcine gut microbiota studies - Hartinger, Kristina; Lerch, Frederike; Yosi, Fitra; Vötterl, Julia C.; Metzler-Zebeli, Barbara U. (Frontiers in Animal Science, 2025)
Aside from being a source of energy and nutrients, a pig’s diet is also a source of microbial DNA, which may be a confounding factor in porcine gut microbiota studies based on DNA sequencing. Therefore, this small-scale pilot study aimed to investigate gene copy numbers, diversity, and taxonomic composition of bacterial DNA present in complete feeds for sows and piglets, including gestation, lactation, and prestarter diets, as well as a milk replacer, and to compare the bacterial communities in feeds for piglets with those in the gastric digesta of piglets consuming these feeds. Total DNA was extracted from feed and gastric samples of piglets for 16S rRNA gene amplicon (V3–V4 region) sequencing. The results showed that the feeds carried a high amount of bacterial DNA, ranging from 8.3 to 9.0 log10 gene copies/g feed. Beta-diversity analysis further indicated clear separation between the bacterial communities in the cereal-based gestation, lactation, and prestarter diets and the milk replacer, whereas alpha-diversity was similar among feeds. Taxonomic evaluation demonstrated that cereal-based feeds were dominated by Pantoea, Pseudomonas, Paenibacillus, and Erwinia, making up 41%–68% of all reads, whereas the milk replacer was dominated by Streptococcus and Lactococcus, with 57.4% and 13.2% relative abundance, respectively. Comparison of the bacterial communities in feed to those in the gastric digesta of piglets on days 3, 7, 14, 21, 28, 31, and 35 of life showed that, although mostly low in abundance, many taxa found in the feed were detectable in gastric digesta. A comparison at the species level is more appropriate to estimate the proportional contribution of bacteria in feed to the total bacterial DNA in gastric digesta. Overall, these data provide valuable insight into the bacterial DNA load and diversity in pig feeds and demonstrate that bacterial DNA found in gastric digesta may be influenced to a small degree by bacteria from the feed.